2019
DOI: 10.1021/acs.macromol.8b02339
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Grafted Molecularly Imprinted Polymers for the Detection of Histamine from Organocatalyzed Atom Transfer Radical Polymerization

Abstract: To be applicable to in vivo measuring, molecularly imprinted polymer (MIP) based sensors need to have high reproducibility, require miniaturization, and must be free of toxic materials (such as heavy metals). To address these requirements, a metal-free photo atom transfer radical polymerization (ATRP) grafting procedure is described using a pulsed UV laser as light source to create thin molecularly imprinted polymer (MIP) films (∼10 nm thickness) on a sensor surface. Analysis via X-ray photoelectron spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Noncore-modified phenoxazines and phenothiazines, possess the conformation similarly to the dihydrophenazines, have been widely used as sufficiently strong reducing OPCs in O-ATRP. 15,19,24,28,29,[40][41][42][43] We thus wondered whether the radial/radial cation cross-coupling process could be also applied in the core modification of phenoxazines and phenothiazines at the 3-and 7-positions of the core of corresponding OPCs. Simplified computational mechanistic studies revealed that these noncore-modified OPCs can couple with the radical species through the radical/radical cation cross-coupling process with reasonable barriers (e.g., < 21.1 kcal/mol), as shown by the black pathways in Fig.…”
Section: Core Modification Of Phenoxazines and Phenothiazinesmentioning
confidence: 99%
“…Noncore-modified phenoxazines and phenothiazines, possess the conformation similarly to the dihydrophenazines, have been widely used as sufficiently strong reducing OPCs in O-ATRP. 15,19,24,28,29,[40][41][42][43] We thus wondered whether the radial/radial cation cross-coupling process could be also applied in the core modification of phenoxazines and phenothiazines at the 3-and 7-positions of the core of corresponding OPCs. Simplified computational mechanistic studies revealed that these noncore-modified OPCs can couple with the radical species through the radical/radical cation cross-coupling process with reasonable barriers (e.g., < 21.1 kcal/mol), as shown by the black pathways in Fig.…”
Section: Core Modification Of Phenoxazines and Phenothiazinesmentioning
confidence: 99%
“…For sensors based on MIP receptors, non-imprinted polymers (NIPs) have been used frequently as a reference. 20,29,41,44 However, a truly nonimprinted polymer is assumed to be less porous than a MIP coating, which poses questions on the comparability. Therefore, we will not only study the response of "true" NIP electrodes to histamine, but also the response of electrodes coated with taurine-imprinted PPy.…”
Section: Considerations On the Sensing Principlementioning
confidence: 99%
“…Because sensor-based assays on complex media can be compromised by nonspecific adsorption, it is common practice to employ differential sensing: the data from a nonfunctional reference channel serve to correct the sensor output for such contributions that may otherwise be registered as false positives. For sensors based on MIP receptors, nonimprinted polymers (NIPs) have been used frequently as a reference. , However, a true NIP is assumed to be less porous than a MIP coating, which poses questions on the comparability. Therefore, we will not only study the response of “true” NIP electrodes to histamine but also the response of electrodes coated with taurine-imprinted PPy.…”
Section: Considerations On the Sensing Principlementioning
confidence: 99%
“…High specific surface area, stability in harsh conditions, and containing suitable functionality, are the factors that are considered for selecting support materials. With respect to type of polymer reagents, various grafting techniques have been applied for anchoring imprinted layer including free-radical grafting [120], living polymerization (atom transfer radical polymerization (ATRP) [121], reversible additionfragmentation chain transfer (RAFT) [97,122]), and photochemical grafting [123]. If detail of each technique is needed, a comprehensive review contributed by Bhattacharya and Misra is recommended for reading [124].…”
Section: Surface Imprinting Based Mipsmentioning
confidence: 99%